2022
DOI: 10.1017/s0014479722000217
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and trinexapac-ethyl effects on wheat grain yield, lodging and seed physiological quality in southern Brazil

Abstract: Summary Nitrogen (N) fertilization affects wheat yield and grain protein concentration; however, its mismanagement can increase plant lodging. While the use of plant growth regulators such as trinexapac-ethyl (TE) can mitigate plant lodging, their effects on seed physiological quality are not well known. The aim of this study was to evaluate the effects of N fertilization and TE on wheat yield, lodging and seed quality of spring wheat varieties. It was carried out in the 2018 growing season in the environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…On the other hand, Yong et al (2004) verified that the falling number was mainly influenced by environmental factors, considering 39 wheat genotypes cultivated in four agroecological zones from China. Therefore, both factors -genotype and environmental conditions -can change the falling number, in addition to influencing other technological quality parameters of wheat flour and grain (Rozbicki et al, 2015;Souza et al, 2021;Faria et al, 2022;Martins et al, 2023), as observed in the present paper.…”
Section: Technological Quality Of Grains and Flour As Influenced By N...supporting
confidence: 54%
See 1 more Smart Citation
“…On the other hand, Yong et al (2004) verified that the falling number was mainly influenced by environmental factors, considering 39 wheat genotypes cultivated in four agroecological zones from China. Therefore, both factors -genotype and environmental conditions -can change the falling number, in addition to influencing other technological quality parameters of wheat flour and grain (Rozbicki et al, 2015;Souza et al, 2021;Faria et al, 2022;Martins et al, 2023), as observed in the present paper.…”
Section: Technological Quality Of Grains and Flour As Influenced By N...supporting
confidence: 54%
“…The aforementioned technological quality traits are defined by wheat genotype, environment, and the genotype × environment interaction, including soil and climate conditions, in addition to being influenced by crop management practices (e.g. fertilization, irrigation, plant growth regulators usage, and control of pests and diseases), harvest process, and drying and storage operations (Blumenthal et al, 1993;Guarienti et al, 2004;Yong et al, 2004;Franceschi et al, 2009;Denčić et al, 2011;Kaya and Akcura, 2014;Rozbicki et al, 2015;Ferreira et al, 2021;Rekowski et al, 2021;Faria et al, 2022). In this context, the supply of essential mineral nutrients by fertilizers is fundamental for the suitable growth and development of wheat plants, favoring the yield and quality of wheat grains and flour (Xue et al, 2016;Ma et al, 2019;Guerrini et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in the high‐input treatment, the synergistic effect of N fertilization, S application, and foliar fungicides may have contributed to positive correlation between yield and GP, which is supported by preliminary evidence where M maintained or improved wheat grain quality (Torrion & Stougaard, 2017; Zecevic et al., 2010). Grain protein is directly influenced by nitrogen management (Daaloul Bouacha et al., 2014; Lollato et al., 2019b, 2021; de Faria et al., 2022; Vazquez et al., 2019), and increased levels of nitrogen available usually increase wheat GP (Mohammed et al., 2013) and wet gluten content (Zecevic et al., 2010). Generally, increases in GP are associated with increases in ω gliadins and high‐molecular‐weight GS but a decrease in α‐, γ‐gliadins and low‐molecular‐weight GS.…”
Section: Discussionmentioning
confidence: 99%